3+4b=-13

Simple and best practice solution for 3+4b=-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+4b=-13 equation:


Simplifying
3 + 4b = -13

Solving
3 + 4b = -13

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 4b = -13 + -3

Combine like terms: 3 + -3 = 0
0 + 4b = -13 + -3
4b = -13 + -3

Combine like terms: -13 + -3 = -16
4b = -16

Divide each side by '4'.
b = -4

Simplifying
b = -4

See similar equations:

| 2(3a-6)=3(2a-4) | | 5=-7+-t | | 2-12x=62 | | x^3+5x^2-6=0 | | 8r-5t=-60 | | -9(x-24)=3(x+24) | | -2(x+9)=12+3x | | 5=18x+6 | | 8x-7+3x-x= | | -13x+18y+10=0 | | 10x+1+10x= | | 48/0.06 | | 5x=6x+48 | | 5x-2+3x-14=0 | | logx=-5.6 | | 2(3x-4)=-22x | | 9 = f3+ 5 | | w^3+7w^2-4w-28=0 | | 3x+5=2(x-5)-x | | f(2)=7x+8 | | 2(x+4)=6x+8 | | 3x+47=122 | | X-0.1X=13 | | -5x+6(x-4)=-16 | | -1/6-(5/8) | | 6(2x-3)-4x+2=4(2x+1)-5 | | -1/8-(5/6) | | 2x^3-27=0 | | 7x-8=x+12 | | 7y-12=6 | | 144=x*4x | | 144=x*2x |

Equations solver categories